Impact of Data Analytics Capabilities on CRM Systems’ Effectiveness and Business Profitability : An Empirical Study in the Retail Industry - Jabado, Roula; Jallouli, Rim (Journal of Telecommunications and the Digital Economy, 2024)
In the current digital era, understanding the role of Data Analytics Capabilities (DAC) in Customer Relationship Management (CRM) systems is essential for businesses seeking better decision-making. While DAC is acknowledged as a Critical Success Factor (CSF) for CRM systems, there is a gap in empirical evidence quantifying its effect on business profitability. This study aims to (1) present the conceptual foundation of the impact of DAC for CRM systems on marketing decisions and business profitability, and (2) empirically estimate the impact of integrating DAC on marketing performance and business profitability. Focusing on the retail sector, the study gathered 131 questionnaires from employees involved in CRM and DAC in Lebanon, and used the SPSS tool for data analysis. The research findings provide advanced empirical evidence of the importance of DAC as a CSF for CRM systems, alongside people, process, and technology dimensions. Results show that the integration of DAC represents a significant step forward in enhancing the effectiveness of CRM systems and achieving better business profitability. This study challenges the conventional understanding of technology’s role in improving business outcomes, thus providing valuable theoretical and practical implications for organizations aiming to enhance their CRM systems.